ANALISIS PENERIMAAN PENGGUNA BUKU SEKOLAH ELEKTRONIK DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL DI KABUPATEN KULON PROGO - , Chris Agung Pramudi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Aspects of user acceptance become one of the main factors that determine the success of the application of information technology. The use of Electronic School Book (BSE) led to a transformation of learning and the way of getting a book, from the manual into an electronic system that cause the attitudes and behaviors of users to receive and use it for real. This study analyzes user acceptance of BSE in the Regency of Kulon Progo, which is measured from the level of user acceptance. Technology Acceptance Model (TAM) is used as a framework for modeling acceptance BSE. Model generated identifies three exogenous variables are: ease of use, usefulness, and behavioral intention to use and four endogenous variables are: subjective norm, system relevance, accessibility quality, and computer selfefficacy. The model was analyzed using Stuctured Equation Modeling (SEM) methods with AMOS 21 program. Results showed that TAM model can explain the factors affecting user acceptance BSE. Based on of 167 teachers as respondents that is BSE users, from the total 10 hypotheses indicate that the accessibility variable quality not significantly affect the perception of usefulness and perceived ease of use of BSE. BSE real usage tends to be low need to encourage the willingness to use BSE with respect to user acceptance variables.